Is aerosol transmission an important risk for PRRSV transmission? An example of how simple biosecurity procedures can prevent virus spread within a barn - B R Trible; Raymond R Rowland R (Kansas Agricultural Experiment Station Research Reports, 2011)
Understanding the transmission of porcine reproductive and respiratory syndrome virus (PRRSV) is important for developing methods to control and eliminate the virus. In this study, 2 similar experiments were performed involving 10 sentinel pigs main- tained for 42 d in close proximity to 190 pigs experimentally infected with a highly pathogenic PRRSV isolate. All pigs were monitored for PRRSV infection by PCR and serology. In the first experiment, virus transmission to sentinel pigs was detected within 21 d after infection of the source population of pigs. In the second experiment, a small separation distance of 27 ft combined with simple biosecurity procedures was sufficient to prevent the transmission of virus to sentinel pigs. Overall, the results indicate a low risk associated with PRRSV spread by aerosols and reinforce the importance of maintaining good biosecurity procedures.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; PRRSV; Aerosols